Beauty and Beautification in Refugees’ Lives and Their Implications for Refugee Policy - Acker, Stephanie (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2023)
This article seeks to understand the significance of everyday beauty in refugees’ lives and its implications for refugee policy; it is one of the first pieces of scholarship to explore this subject in this context. A review of the existing literature on beauty in refugee contexts followed by a deductive analysis of the literature on refugee homemaking demonstrates how beauty and beautification play an active role in how refugees (re)make home, even in temporary situations. Beauty is used to build hope, celebrate culture, create community, and honour past and present realities, and therefore has significant implications for the objectives of the Global Compact on Refugees. The role of beauty in refugee homemaking suggests challenging the narrow focus on durable solutions to a more holistic framework, transforming language and policy approaches to include refugees as decision-makers, and investing in the quality of shelters, camps, and homes as a more effective way to reduce pressure on host countries.